Comparison of frequency of Hypoparathyroidism in Total Thyroidectomy (TT) versus Near-Total Thyroidectomy (NTT) patients - Sajid Rehman Randhawa; Muhammad Saleem Iqbal; Tayyaba Fatima; Iqra Khalid; Muhammad Sajid (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Hypoparathyroidism in total thyroidectomy and near-total thyroidectomy is debatable. This study will determine the procedure of choice. Our objective is to compare the frequency of hypoparathyroidism in total thyroidectomy versus near-total thyroidectomy patients.METHODOLOGY: Prospective observational study was conducted at the Department of Surgery, Allied Hospital, Faisalabad. The study duration was six months. A total of 140 patients having multinodular goiter, 30-70 years of age, were selected. Patients were divided into two groups. In group A; patients underwent total thyroidectomy while in group B; patients were offered near-total thyroidectomy. All the parathyroid glands were preserved. In all patients, serum calcium levels and parathyroid hormone (PTH) levels were checked on 1st & the 2nd day after surgery.RESULTS: Mean age in group A was 48.06±8.21 years & in group B was 48.83 ± 7.0 years. The majority of patients, 88 (62.86%) were between 30 to 50 years of age. Out of these 140 patients, 37 (26.43%) were males & 103 (73.57%) were females, with the ratio of 1:2.8. Mean pre-operative serum Parathyroid hormone was 25.67±9.87 pg/mL. The mean postoperative serum Parathyroid hormone was 16.87±2.43 pg/mL. Mean pre-operative serum calcium levels were 11.32 ± 4.52 mg/dl and mean postoperative serum calcium levels were 9.4 ±0.45mg/dl. In this study, the frequency of Hypoparathyroidism in the total thyroidectomy group (28.57%) was significantly higher than near-total thyroidectomy (8.57%) (p=0.002).CONCLUSION: Hypoparathyroidism is more common after total thyroidectomy as compared to near-total thyroidectomy.